I Wonder Why Triceratops Had Horns : and other questions about our planet - Anita Ganeri (U.S.A Kingfisher)
Children are fascinated by the world around them, and why is a favourite word. This series takes as its starting point this natural desire to understand the world, and then feeds it with text and illustrations designed both to entertain and to inform. This book focuses on the earth sciences and covers topics such as how high the sky is and how to tell whether an earthquake is coming.
Keywords: Animal; Living Things -- Living Things; Dinosaurs (Extinct Animals) -- Dinosaurs (Extinct Animals)